Extracorporeal Cardiopulmonary Resuscitation in Adults. Interim Guideline Consensus Statement From the Extracorporeal Life Support Organization - Richardson, Alexander Sacha C; Tonna, Joseph E; Nanjayya, Vinodh; Nixon, Paul; Abrams, Darryl C; Raman, Lakshmi; Bernard, Stephen; Finney, Simon J; Grunau, Brian; Youngquist, Scott T; McKellar, Stephen H; Shinar, Zachary; et al. (ASAIO journal (American Society for Artificial Internal Organs, 2021)
Veno-arterial extracorporeal membrane oxygenation (ECMO) is increasingly being deployed for selected patients in cardiac arrest who do not attain a native circulation with conventional CPR (ECPR). This ELSO guideline is intended to be a practical guide to implementing ECPR and the early management following establishment of ECMO support. Where a paucity of high-quality evidence exists, a consensus has been reached amongst the authors to provide guidance to the clinician. This guideline will be updated as further evidence in this field becomes available.
Keywords: Cardiopulmonary Resuscitation; kardiopulmonální resuscitace; Heart Arrest; mužské pohlaví; Humans; Patient Selection; Consensus; srdeční zástava; Male; lidé; konsensus; výběr pacientů